2020
DOI: 10.3390/jcm9041034
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Diseases and Osteoporosis

Abstract: Thyroid hormones are essential for normal skeletal development and normal bone metabolism in adults but can have detrimental effects on bone structures in states of thyroid dysfunction. Untreated severe hyperthyroidism influences the degree of bone mass and increases the probability of high bone turnover osteoporosis. Subclinical hyperthyroidism, defined as low thyrotropin (TSH) and free hormones within the reference range, is a subtler disease, often asymptomatic, and the diagnosis is incidentally made during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(103 citation statements)
references
References 99 publications
0
95
0
8
Order By: Relevance
“…Main targets are the middle-aged and elderly people over the age of 50. The occurrence of osteoporosis can be linked to other endocrine morbidities, like diabetes, obesity, thyroid hormone disease ( Dolan et al, 2017 ; Tanaka et al, 2018 ; Delitala et al, 2020 ; Zou et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Main targets are the middle-aged and elderly people over the age of 50. The occurrence of osteoporosis can be linked to other endocrine morbidities, like diabetes, obesity, thyroid hormone disease ( Dolan et al, 2017 ; Tanaka et al, 2018 ; Delitala et al, 2020 ; Zou et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the exact mechanisms are not yet clear and deserve further exploration [15]. Moreover, it has been suggested that thyroid autoimmunity was a potential marker of higher fracture risk in patients with subclinical hypothyroidism [29,30]. It is estimated that autoimmune disease is present in approximately 10-40% of patients with POI [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis showed that smoking increased the risk of Graves' disease 114 . Overt thyroid toxicosis is known to reduce bone mass through high remodelling 115 . Smoking is also associated with higher cortisol in the morning and throughout the day in a cohort of elderly 116 .…”
Section: Factors Mediating the Relationship Between Psychological Strmentioning
confidence: 99%